2018
DOI: 10.3390/math6050077
|View full text |Cite
|
Sign up to set email alerts
|

The “Lévy or Diffusion” Controversy: How Important Is the Movement Pattern in the Context of Trapping?

Abstract: Many empirical and theoretical studies indicate that Brownian motion and diffusion models as its mean field counterpart provide appropriate modeling techniques for individual insect movement. However, this traditional approach has been challenged, and conflicting evidence suggests that an alternative movement pattern such as Lévy walks can provide a better description. Lévy walks differ from Brownian motion since they allow for a higher frequency of large steps, resulting in a faster movement. Identification o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…In the context of trapping, it was recently shown that almost identical trap counts are reproduced for inherently different movement models, such as BM with time dependent mobility rate and the LW, which suggests that the type of underlying movement pattern is not that important after all, unless placed under some ecological context, e.g. pest monitoring (Ahmed et al., ). Although controversy persists, our motivation for including LWs stems from the fact that such mechanistic processes have received much attention in the movement ecology literature (Reynolds, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of trapping, it was recently shown that almost identical trap counts are reproduced for inherently different movement models, such as BM with time dependent mobility rate and the LW, which suggests that the type of underlying movement pattern is not that important after all, unless placed under some ecological context, e.g. pest monitoring (Ahmed et al., ). Although controversy persists, our motivation for including LWs stems from the fact that such mechanistic processes have received much attention in the movement ecology literature (Reynolds, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, other more complicated processes have been documented, such as; intermittent stop‐start movement (Mashanova, Olive, & Jansen, ), behavioural intensive‐extensive changes (Knell & Codling, ), individual interactions (De Jager, Weissing, Herman, Nolet, & de Koppel, ), density or time dependent diffusion (Ahmed & Petrovskii, ; Ellis, Petrovskaya, & Petrovskii, ), Lévy walks (LW; Sims et al., ) or even a mixture or composition of the above (Auger‐Méthé, Derocher, Plank, & Codling, ). The issue is more perplexing, since movement patterns can be misidentified (Petrovskii, Mashanova, & Jansen, ) or even, in the context of trapping, almost identical trap counts can be reproduced for inherently different movement models (Ahmed, Petrovskii, & Tilles, ). Also, the conceptual case of BM is often revisited due to its relative simplicity and on occasion shown to be in excellent agreement with field data (Bearup et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The x min value, in this case, was set at the smallest non-zero value of the data rather than the value for x min calculated by power.law.fit function (Virkar and Clauset, 2014). Secondly, a power-law fitting only the tail of the data was considered as this is an indicative feature of Lévy walk behaviour (Edwards et al ., 2007; Sims et al ., 2007; Reynolds et al ., 2013; Ahmed et al ., 2018). The tail of the data was calculated by using the best fit x min value calculated by the power.law.fit() function.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of movement behaviours can be characterized by the rate of asymptotic decay in the end tail of the step length distribution λ (l). If the end tail decays exponentially or faster (referred to as a 'thin' tail), then the variance of step lengths is finite, and therefore the movement process is scale-specific and diffusive (Kareiva and Shigesada, 1983;Codling et al, 2008;Ahmed et al, 2018). See for example, the case of the SRW with Rayleigh distributed step lengths in equation 5.…”
Section: The Correlated Lévy Walkmentioning
confidence: 99%